2007
DOI: 10.1038/nn1908
|View full text |Cite
|
Sign up to set email alerts
|

Synapse formation on neurons born in the adult hippocampus

Abstract: Although new and functional neurons are produced in the adult brain, little is known about how they integrate into mature networks. Here we explored the mechanisms of synaptogenesis on neurons born in the adult mouse hippocampus using confocal microscopy, electron microscopy and live imaging. We report that new neurons, similar to mature granule neurons, were contacted by axosomatic, axodendritic and axospinous synapses. Consistent with their putative role in synaptogenesis, dendritic filopodia were more abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
472
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 509 publications
(529 citation statements)
references
References 50 publications
41
472
1
3
Order By: Relevance
“…Imipramine and fluoxetine have been shown to increase both neuronal proliferation and survival in the adult hippocampus via activation of trkB/BDNF signaling: mice deficient in BDNF do not show enhanced neuronal survival after antidepressant treatment (Sairanen et al, 2005). Fluoxetine also promotes plasticity in the hippocampus by increasing pyramidal neuron dendritic spine density (Hajszan et al, 2005), which may provide a general enhancement of the synaptic input that new neurons require for survival and network integration (Kee et al, 2007;Toni et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Imipramine and fluoxetine have been shown to increase both neuronal proliferation and survival in the adult hippocampus via activation of trkB/BDNF signaling: mice deficient in BDNF do not show enhanced neuronal survival after antidepressant treatment (Sairanen et al, 2005). Fluoxetine also promotes plasticity in the hippocampus by increasing pyramidal neuron dendritic spine density (Hajszan et al, 2005), which may provide a general enhancement of the synaptic input that new neurons require for survival and network integration (Kee et al, 2007;Toni et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…these include precursors for membrane phosphatidylation such as uridine, choline and omega-3 polyunsaturated fatty acids (4)(5)(6). Reports have also indicated that combining these nutrients may improve cognition and increase hippocampal dendritic spines (7), again suggesting a positive effect on the formation of new synapses (8)(9)(10). it was therefore hypothesized that such agents may play a role in the management of ad.…”
mentioning
confidence: 99%
“…Young adult rats generate ~9000 new cells in the SGZ daily; approximately half of them survive (Cameron and McKay, 2001). The surviving cells develop synaptic connections with the entorhinal cortex and the CA3 subfield, thereby integrating into the existing neuronal circuits (van Praag et al, 2002;Toni et al, 2007).…”
Section: Neurogenesis In the Adult Mammalian Brainmentioning
confidence: 99%